Keabsahan Pemungutan Pajak Hotel Atas Jaringan Perhotelan OYO Rooms - Muhammad Zata Mahardika (Faculty of Law, Universitas Airlangga, 2022)
AbstractHotel tax is a big tax potential for the state, especially for the regions. Indonesia is a country with a very large potential for the hospitality industry, this is indicated by the high level of both local and foreign tourists, thus encouraging the rapid development of the hospitality industry. The hotel industry is one of the great potential for government revenue, through hotel taxes. Along with the entry of the industry 4.0, with its disruption, which is marked by the rapid development of technology in the world of industry and business in Indonesia, business actors, both the Indonesian people and the global community, have begun to take advantage of technological developments in running their business, including Hotel Business. OYO Rooms is an online-based hotel network company, by providing booking services for lodging facilities that can be done through an application that can be downloaded on the smartphone or through the internet site (website).Keywords: Tax Collection; Hotel Tax; E-Commerce; OYO Rooms. AbstrakPajak Hotel merupakan potensi pajak yang besar bagi negara, khususnya bagi daerah. Indonesia merupakan negara dengan potensi industri perhotelan yang sangat besar, hal ini ditandai dengan tingginya tingkat wisatawan lokal maupun mancanegara, sehingga mendorong berkembang pesatnya industri perhotelan. Industri perhotelan ini menjadi salah satu potensi pendapatan pemerintah yang besar, melalui pajak hotel. Seiring dengan masuknya era industri 4.0, yang ditandai dengan berkembang pesatnya teknologi dalam dunia industri dan bisnis di Indonesia, maka para pelaku usaha baik masyarakat Indonesia maupun masyarakat global mulai memanfaatkan perkembangan teknologi dalam menjalankan usahanya, termasuk Usaha Hotel. OYO Rooms merupakan perusahaan jaringan perhotelan dengan berbasis online, dengan menyediakan layanan pemesanan fasilitas penginapan tersdapat dilakukan melalui aplikasi yang dapat diunduh di gawai atau melalui situs internet (website).Kata Kunci: Pemungutan Pajak; Pajak Hotel; E-Commerce; OYO Rooms.